World history from the ancient world to the information age - Parker, Philip 1965- (Dorling Kindersley Limited, 2017)
Discover the events that have shaped our world, from the dawn of prehistoric civilization to the digital age, brought to life with contemporary photographs, maps, paintings, and artifacts that place each event in a wider social and historical context.